FGF1 as a New Promising Therapeutic Target in Type 2 Diabetes: Advances in Research and Clinical Trials - Bu T; Gao X; Zhang R; Xu Y (Diabetes, Metabolic Syndrome and Obesity)
Tiansheng Bu,* Xiaojuan Gao,* Ruina Zhang, Ying Xu Department of Traditional Chinese Medicine, The Third Affiliated Hospital of Gansu University of Chinese Medicine, Baiyin, Gansu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ying Xu, Department of Traditional Chinese Medicine Management, The Third Affiliated Hospital of Gansu University of Chinese Medicine, Baiyin, Gansu, People’s Republic of China, Email 18009432685@163.comAbstract: Type 2 diabetes mellitus (T2DM) represents a global health crisis, characterized by insulin resistance, β-cell dysfunction, and metabolic disturbances. Current treatments, such as insulin and metformin, often fail to address the dual challenges of β-cell preservation and insulin resistance, leading to suboptimal long-term outcomes. Fibroblast growth factor 1 (FGF1) has recently gained attention as a new promising therapeutic target due to its unique ability to regulate glucose homeostasis, enhance insulin sensitivity, and protect β-cells without inducing hypoglycemia. This review critically examines the mechanisms of FGF1 action, including its signaling pathways, interactions with metabolic regulators, and roles in key organs involved in glucose metabolism. Additionally, we summarize findings from preclinical and clinical studies and evaluate the challenges associated with its therapeutic application, including pharmacokinetic limitations, delivery strategies, and long-term safety concerns. By addressing these issues, FGF1 holds the potential to advance beyond symptom management to become a disease-modifying therapy for T2DM.Keywords: FGF1, T2DM, insulin sensitivity, β-cell protection